Perceptions of Hochelaga-Maisonneuve Neighborhood in Montreal: A Textual Analysis of Written Media - Paré, Sylvie; Mounier, Sandrine (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2020)
Many authors have documented the increasing diversification and gentrification in central city neighbourhoods. In the last few decades Montreal’s, Hochelaga-Maisonneuve is among those with the highest rates of gentrification, creating new social dynamics and often generating socio-territorial conflicts. What is the significance of social changes for the population of Hochelaga-Maisonneuve? What role does recent immigration play in the mitigation or development of social conflict? In this paper we present the results of the analysis of 1,420 articles taken from the six principal daily newspapers published in Montreal. In our target neighbourhood, it would appear that a higher socio-economic status of newcomers is more disruptive than their ethno-cultural background because it is associated with a change in the way people live, shop and interact in public space. The data also reveal disruptive effects on the availability of affordable housing, a feature that means increasing displacement of lower income populations.